Climate‐ versus geographic‐dependent patterns in the spatial distribution of macroinvertebrate assemblages in New World depressional wetlands. (13th October 2020) - Stenert, Cristina; Pires, Mateus M.; Epele, Luis B.; Grech, Marta G.; Maltchik, Leonardo; McLean, Kyle I.; Mushet, David M.; Batzer, Darold P.
Abstract: Analyses of biota at lower latitudes may presage impacts of climate change on biota at higher latitudes. Macroinvertebrate assemblages in depressional wetlands may be especially sensitive to climate change because weather‐related precipitation and evapotranspiration are dominant ecological controls on habitats, and organisms of depressional wetlands are temperature‐sensitive ectotherms. We aimed to better understand how wetland macroinvertebrate assemblages were structured according to geography and climate. To do so, we contrasted aquatic‐macroinvertebrate assemblage structure (family level) between subtropical and temperate depressional wetlands of North and South America using presence–absence data from 264 of these habitats across the continents and more‐detailed relative‐abundance data from 56 depressional wetlands from four case‐study locations (North Dakota and Georgia in North America; southern Brazil and Argentinian Patagonia in South America). Both data sets roughly partitioned wetland numbers equally between the two climatic zones and between the continents. We used ordination methods (PCA and NMDS) and tests of multivariate dispersion (PERMDISP) to assess the distribution and the homogeneity in variation in the composition of macroinvertebrate assemblages across climates and continents, respectively. We found that macroinvertebrate assemblage structures in the subtropical depressional wetlands of North and South America were similar to each other (at the family level), while assemblages in the North and South American temperate wetlands were unique from the subtropics, and from each other. Tests of homogeneity of multivariate dispersion indicated that family‐level assemblage structures were more homogeneous in wetlands from the subtropical than the temperate zones. Our study suggests that ongoing climate change may result in the homogenization of macroinvertebrate assemblage structures in temperate zones of North and South America, with those assemblages becoming enveloped by assemblages from the subtropics. Biotic homogenization, more typically associated with other kinds of anthropogenic factors, may also be affected by climate change. Abstract : We assessed wetland macroinvertebrate community compositions across the subtropical and temperate zones of North and South America, using meta‐analyses (264 wetlands) and more‐detailed case studies (56 wetlands in North Dakota, Georgia, Brazil, Argentina). Assemblages in the subtropics were homogeneous across both continents, while assemblages across the two temperate zones were more unique and more heterogeneous; climate appears to be a primary control on assemblage structure. In the context of climate change, differences between the subtropical and temperate zones may presage the impacts of ongoing warming, where the homogeneity of the subtropics may envelop the heterogeneity of the temperate zones.